Across-arc variation of the Famatinian magmatic arc (NW Argentina) exemplified by I-, S- and transitional I/S-type Early Ordovician granitoids of the Sierra de Velasco - Grosse, Pablo (2011)
The Early Ordovician granitoids of the Sierra de Velasco reflect the across-arc compositional variation of the Famatinian magmatic arc (NW Argentina) developed along the proto-Andean margin of western Gondwana. This variation is characterized by means of field, petrographical, geochemical and isotopic studies. The Sierra de Velasco contains three main types of Early Ordovician granitoids that are mineralogically and geochemically distinct, but generally conform a continuous high-K, magnesian and calcalkalic magmatic series. I-type granitoids (IG) make up the southern part of the range. They are biotite-hornblende-titanite metaluminous to weakly peraluminous granodiorites and tonalites typical of a coastal I-type belt and were possibly formed by melting of mafic lower crust/lithospheric mantle, with minor assimilation of crustal metasediments. S-type granitoids (SG) crop out in the central and northern portions of the range. They are biotite-muscovite and biotite-cordierite strongly peraluminous syeno- and monzogranites representative of an inland S-type belt and were possibly formed by large-scale anatexis of metasedimentary crust and hybridization with more mafic lower crustal melts. Between the IG and SG, in the central parts of the range, transitional I/S-type granitoids (TG) are recognized that consist of biotite, biotite-muscovite and subordinate biotite-titanite-allanite-epidote moderately peraluminous monzogranites, granodiorites and tonalites. The TG show intermediate characteristics and were possibly generated by less common mechanisms of mixing between I-type and S-type magmas and/or their parent mafic lower crustal and metasedimentary melts. The transition from IG to TG to SG towards the continental interior reflects a compositional continuum related to a progressive variation in the degrees of mixing between mafic and metasedimentary end-members.